If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -21x = 0 Combine like terms: -3x + -21x = -24x -24x = 0 Solving -24x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-24'. x = 0 Simplifying x = 0
| 6x+7=-131 | | 0.5(4x+6)=0.33(9x-24) | | 4x+6=6x-14 | | 8x+32=4x+8 | | (7x-10)-(-6x+8)= | | 52x=208 | | 8*-1=m | | 121x^2-132x-27=0 | | x^4+8x^3+15x^2-8x-16=0 | | 14d+30=-196 | | 168=x+3x | | 3x+9=4x-2 | | 2(x-5)+5x=88 | | x^3-6x^2-24x-9=0 | | 6qr-10t=5u | | -x^2-2x+3=1 | | 50x+75=65 | | 8x-11+5x=13 | | x+3x=26408 | | 3m+21=-6 | | (4x+13)-11= | | 2(3x-4)+6=7x+6(4-2x) | | 3x-14+2x+28=80 | | 30x-90=20x+50 | | x-3.7=5.25 | | 7y-8=41 | | 8x-11+5x=24 | | 4y+9=36 | | (y+5)=7 | | 9x+6+4x= | | 5x-7-2x+15=47 | | [27x-787]+18=9 |